The Prevalence Of Mental Disorders And Associated Out-Ofpocket Expenditure Among Insured Patients In South Africa - Mnangagwa, Mazvita (Adolescent Health Research Institute, 2024)
Mental disorders are a huge global burden, with approximately a quarter of the population developing a mental illness at some point. Despite significant advances in treatment for these disorders, massive treatment gaps still exist. In South Africa, approximately 20% of adults are believed to be struggling with poor mental health, with less than a quarter of this population ever receiving mental health care. A potential strategy for reducing such treatment gaps is private health insurance (PHI). Around 18% of the total South African population is medically insured. PHI, however, only covers a restricted set of expenses. The aim of this study is to examine the prevalence of mental disorders and the out-of-pocket costs among South African insured individuals. Discovery Health Medical Scheme (DHMS) population was used as a proxy for the private health insurance market in South Africa. DHMS is South Africa's largest medical scheme with a 56.7% market share as of 2019. STATA version 17 and Excel were used to analyse the data on five common mental disorders (depression, anxiety disorders, bipolar, development and learning disorder, and attention deficit and hyperactivity disorder) over a 36-month period. Children and adults with or without comorbidities and with no gender restrictions were included.